A new genus and species of Atalophlebiinae (Insecta: Ephemeroptera: Leptophlebiidae) from Palni hills of the southern Western Ghats, India - Selvakumar, C.; Sivaruban, T.; Subramanian, K. A.; Sivaramakrishnan, K. G. (Zootaxa, 2016)
A new genus and new species of Atalophlebiinae, Klugephlebia kodai Selvakumar, Subramanian & Sivaramakrishnan, are described based on male and female imagos and larvae from Palni hills of the southern Western Ghats of India. The imago of Klugephlebia gen. n. can be differentiated from all other genera of Atalophlebiinae by having the combination of vein MP forked slightly less than half of the distance from base to margin, MP2 attached at base to vein MP1 by a crossvein, a distinctive shape of the hindwing, dissimilar claws on each leg, and distinctive genitalia structures. The larva can be distinguished from other Atalophlebiinae larvae by having the combination of gills present on abdominal segments 1–7, dorsal and ventral portions of lamellae of gills 1 slender and lanceolate with branched tracheae, dorsal and ventral portions of lamellae of gills 2–7 wider & lanceolate and long & suddenly tapering at apex, fore and mid femora with regular rows of long thin setae on outer margins, denticles on claws progressively larger apically, a distinctive labrum, the maxillary palp short with long setae on third segment, and the third segment of the labial palp with distinct setation. The larvae cling to the underside of boulders in the middle of streams where the boulders lie amidst sand and silt. Updated keys to the genera of south Indian Leptophlebiidae are provided.